Rice Husk Packed Bed Column Reactor To Remove Cadmium From Landfill Leachate - Monik Kasman; Shaliza Ibrahim; Salmariza Salmariza (Jurnal Litbang Industri, 2014)
The landfill leachate can be a major problem due to large variability of high organic, inorganic, heavy metal content and toxicity characteristics from landfill leachate such as  cadmium. Thus, this study was aimed to observe the application of rice husk packed bed column to reduce cadmium from landfill leachate. Experiment was conducted in gravity down flow system by pumping landfill leachate into packed bed column. The effect of influent flow rate to adsorption capacity was studied by varying flow rate (5 mL/min and 10 mL/min). The effluent-influent concentration ratio Ce/C0 (%) as a function of throughput volume (L) was used to represent the breakthrough curve in column systems. Result shows that the flow rate of 5 mL/min was favorable to achieve higher removal rates with the percentage of cadmium was 57 %. At breakthrough time, the cadmium effluent concentration reached on 0.01 mg/l for both of flow rate.ABSTRAKLindi yang dihasilkan dari TPA (Tempat Pembuangan Akhir) menimbulkan permasalahan lingkungan karena kandungan pencemarnya meliputi material organik, material anorganik, logam dan material beracun. Salah satu logam berat yang terdapat dalam lindi tersebut adalah kadmium. Penelitian ini bertujuan untuk mereduksi kadmium dalam lindi dengan menggunakan sekam padi yang diinstal dalam packed bed column. Lindi dipompakan dari tangki penampung lindi ke dalam packed bed column dan dialirkan dari atas ke bawah kolom secara gravitasi. Fokus pada penelitian ini adalah pengaruh laju alir influen terhadap kapasitas adsorpsi. Dimana lindi dialirkan dengan laju alir 5 mL/menit dan 10 mL/menit. Kurva breakthrough (titik jenuh) kolom dipresentasikan oleh hubungan antara rasio konsentrasi efluen-influen Ce/C0 (%) dan jumlah aliran lindi yang diolah dalam kolom. Hasil eksperimen menunjukkan bahwa persentase reduksi tertinggi dicapai pada laju alir 5 mL/menit yaitu 57%. Waktu jenuh kedua laju alir (5 mL/menit dan 10 mL/menit) tercapai saat konsentrasi efluen kadmium 0.01 mg/L.